Sustainable development in production and consumption of products. Beyond Club of Rome and Summit of Rio: how far have we come?. (1st January 2000) - Warnecke, Hans-Jurgen; Eyerer, Peter
This article gives an account of the state of the art of sustainable development with a focus on Germany. The discussion considers different aspects such as protection of non-renewable materials and energy, material flow management, re-use of products and environmental management under economical aspects, and leads to the recognition of a need for action. To prevent a departure from sustainable development, caused by the nations' economic fight for survival, a change in politics and education is required. Apart from technical and economical aspects, new social and ecological ways in our behaviour must be implemented. Rich industrial nations should take responsibility for sustainable development by redistribution of investments on a global basis. Investments in environmental technology in developing countries would lead to a higher reduction of emissions compared with the same amount of investment in western countries. Furthermore, the internalisation of environmental costs must be implemented, those responsible for pollution have to be liable for the resulting damage. The environment as common property needs to be valued. To strengthen the idea of sustainability the next generations should be taught this concept. The German education system needs to teach practical project work. Students should be trained in project management by working on industrial R&D problems. The organisation of a network integrating industry with schools and universities would innovate education. Such networks also need special tools for life cycle assessment in order to establish sustainable development in education systems. The practical conversion to sustainable development therefore demands severe social changes. In this article, a vision for the realisation of this task is created.